A new Andean lizard of the genus Potamites (Sauria, Gymnophthalmidae) from Manu National Park, southeastern Peru - Chávez, Germán; Catenazzi, Alessandro (Zootaxa, 2014)
We describe a new lizard of the genus Potamites from elevations of 1000–2100 m in the montane forests of the Cordillera de Paucartambo and the upper Kosñipata valley, Region of Cusco, Peru. The new species differs from other species of Potamites by having scattered keeled scales on dorsum, an undivided frontonasal and absence of femoral pores in females.